Potential Implications of Natural Antioxidants of Plant Origin on Oxidative Stability of Chicken Albumen during Storage: A Review - Uchechukwu Edna Obianwuna; Vivian U. Oleforuh-Okoleh; Jing Wang; Hai-Jun Zhang; Guang-Hai Qi; Kai Qiu; Shu-Geng Wu (MDPI AG, 2022)
Enhanced albumen quality is reflected in increased thick albumen height, albumen weight, and Haugh unit value, while the antimicrobial, antioxidant, foaming, gelling, viscosity, and elasticity attributes are retained. Improved albumen quality is of benefit to consumers and to the food and health industries. Egg quality often declines during storage because eggs are highly perishable products and are most often not consumed immediately after oviposition. This review provides insights into albumen quality in terms of changes in albumen structure during storage, the influence of storage time and temperature, and the mitigation effects of natural dietary antioxidants of plant origin. During storage, albumen undergoes various physiochemical changes: loss of moisture and gaseous products through the shell pores and breakdown of carbonic acid, which induces albumen pH increases. High albumen pH acts as a catalyst for structural changes in albumen, including degradation of the β-ovomucin subunit and O-glycosidic bonds, collapse of the ovomucin-lysozyme complex, and decline in albumen protein-protein interactions. These culminate in declined albumen quality, characterized by the loss of albumen proteins, such as ovomucin, destabilized foaming and gelling capacity, decreased antimicrobial activity, albumen liquefaction, and reduced viscosity and elasticity. These changes and rates of albumen decline are more conspicuous at ambient temperature compared to low temperatures. Thus, albumen of poor quality due to the loss of functional and biological properties cannot be harnessed as a functional food, as an ingredient in food processing industries, and for its active compounds for drug creation in the health industry. The use of refrigerators, coatings, and thermal and non-thermal treatments to preserve albumen quality during storage are limited by huge financial costs, the skilled operations required, environmental pollution, and residue and toxicity effects. Nutritional interventions, including supplementation with natural antioxidants of plant origin in the diets of laying hens, have a promising potential as natural shelf-life extenders. Since they are safe, without residue effects, the bioactive compounds could be transferred to the egg. Natural antioxidants of plant origin have been found to increase albumen radical scavenging activity, increase the total antioxidant capacity of albumen, reduce the protein carbonyl and malondialdehyde (MDA) content of albumen, and prevent oxidative damage to the magnum, thereby eliminating the transfer of toxins to the egg. These products are targeted towards attenuating oxidative species and inhibiting or slowing down the rates of lipid and protein peroxidation, thereby enhancing egg quality and extending the shelf life of albumen.